Processamento de empanado de frango adicionado de surimi e inulina e reduzido de sódio - Libardi, Manoela Cassa (2015)
Consumers have searched for practical products to prepare and with healthy appeal. Surimi can be used in meat products because it has high nutritional quality and economic appeal. The fibers can be added to meat products to improve their nutritional intake. For the reduction of sodium in foods, potassium chloride is used as substitute. The objective of this study was to obtain surimi from fresh fish and prepare nuggets with added surimi (0% to 4%), inulin (0% to 6%) and reduced sodium chloride, with 0% to 100% replacement of sodium chloride. The products were evaluated by physicochemical characteristics (moisture, protein, fat, ash, carbohydrates and energy), technological (water retention capacity-WRC, weight loss, dimensional shrinkage, cook yield, texture profile, pH and color), in sensory tests (acceptance testing and purchase intent) and microbiological analyses. It was performed a comparison to trademarks as the moisture, protein, fat, ash, dietary fiber, sodium, carbohydrates and energy. Word association test was performed to verify the main associations of consumers with healthier concepts of chicken nuggets. It was calculated the desirability function to optimize the formulations. The addition of surimi and inulin resulted in increased WRC of the formulations, while the full replacement of sodium chloride by potassium chloride resulted in the reduction of this variable. It has also been observed the influence of sodium chloride on the dimensional shrinkage and cook yield as well as texture. The addition of surimi and inulin and the reduction of sodium chloride by substitution with potassium chloride resulted in nuggets with better technological characteristics when compared to the control nuggets processing, demonstrating the advantages of their use. All treatments showed pH value within the limits set by law. The higher scores for the sensory attributes were observed in the formulation containing 2% of surimi, 3% inulin and replacement of 50% of sodium chloride by potassium chloride, while scores decreased with the complete replacement of sodium chloride with potassium chloride. In word association test, the terms used in the preparation of concepts (addition of protein and fiber and sodium reduction) have led to the perception of healthier products. The formulation 15 of this study (2% of surimi, 3% of inulin and 50% replacement of sodium chloride by potassium chloride) obtained sodium and fat content inferior and protein and fiber content superior than trademarks, with healthier characteristics in respect to nutrient content. The results of microbiological analysis met the standards set by law. For the desirability function, were used variables flavor, texture, global impression, purchase intent and protein content. Individual desirability of each variable and the overall desirability was calculated. The maximum overall desirability was 0.980.